Exercise interventions in child and adolescent mental health care: An overview of the evidence and recommendations for implementation - Rebekah Carney; Joseph Firth (Wiley, 2021)
Abstract Background The use of physical activity interventions in mental health care for adults has a large academic evidence base and numerous examples of real‐world implementation. However, the use of physical activity within mental health care for children and young people (CYP) has received less attention to date. Methods A narrative review was conducted to summarize the relevant literature in the area. Online databases were searched using terms synonymous with CYP, exercise, physical health, and mental health. Findings from existing systematic reviews, meta‐analyses, meta‐syntheses, and consensus statements were reviewed, and used alongside the authors' experience to inform clinical recommendations. Results We first discuss the importance of applying physical health interventions in early stages of mental illness for CYP to prevent physical comorbidities and premature mortality in the long term. We then provide a brief summary of the current evidence of the benefits of exercise interventions in CYP with mental illness. We then present our top five recommendations on the implementation of exercise interventions within CYP mental health care. Conclusion The key conclusions from this suggest there is an increasingly strong evidence base for the benefits of using physical activity interventions to improve, prevent, and manage physical and mental health outcomes in CYP with mental illness. However, more work needs to be done to improve the evidence base, refine its implementation into standard mental health care, and develop strategies for large‐scale dissemination of such interventions across various care and cultural contexts.